Facile Synthesis of Large‐Pore Bicontinuous Cubic Mesoporous Silica Nanoparticles for Intracellular Gene Delivery. Issue 3 (2nd February 2016) - Meka, Anand Kumar; Niu, Yuting; Karmakar, Surajit; Hartono, Sandy Budi; Zhang, Jun; Lin, Chun Xiang Cynthia; Zhang, Hongwei; Whittaker, Andrew; Jack, Kevin; Yu, Meihua; Yu, Chengzhong
Abstract: Mesoporous silica nanoparticles (MSNs) have promising biomedical applications; however the synthesis of MSNs with a bicontinuous cubic Ia 3 d mesostructure and large pore size has been a long‐standing challenge. Herein we report a systematic study on the synthesis of KIT‐6 type MSNs (KIT‐6‐MSNs) using fluorocarbon‐hydrocarbon mixed surfactants as templates and ethanol as a co‐solvent. KIT‐6‐MSNs have a pore size of 9 nm and a particle size in the range of 200–400 nm. The role of ethanol in the synthesis of KIT‐6‐MSNs is crucial because ethanol increases the miscibility of fluorocarbon and hydrocarbon surfactants, thereby increasing the packing parameter and favoring the formation of an Ia 3 d structure. Excessive fluorocarbon surfactants help the formation of nanosized morphology. After hydrophobic modification, the large‐pore KIT‐6‐MSNs show a high loading capacity towards genetic molecules and successfully deliver the survivin siRNA into a human colorectal carcinoma HCT116 cell line, knocking down the gene expression associated with cancer cell survival and proliferation. Abstract : Special delivery : A novel and facile approach has been developed to synthesize KIT‐6 type mesoporous silica nanoparticles (KIT‐6‐MSNs) with a bicontinuous cubic Ia 3 d mesostructure and large pore size (9 nm) and small particle size (200–400 nm). After octadecyl group (C18 ) modification, KIT‐6‐MSNs‐C18 have demonstrated successful delivery of survivin siRNA into human colon cancer cells (HCT‐116) and efficient suppression of survivin protein, causing a significant inhibition of cell proliferation.